1992
DOI: 10.1002/ajim.4700220609
|View full text |Cite
|
Sign up to set email alerts
|

Upper extremity symptoms in supermarket workers

Abstract: Upper extremity symptoms in supermarket workers, particularly those who performed checking using laser scanners, were evaluated using a questionnaire administered by trained interviewers to 124 supermarket workers. Summary indices of exposure (short-term and long-term) as well as indices of past personal illnesses and personal activities were employed. Outcome data were summarized by four composite symptom indices. Chi square and logistic regression analyses demonstrated that hours of checking work in the prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…Whether this age effect [Stetson et al, 19921 is solely due to the biological aging effect or related to the length of exposure years is difficult to determine. Health surveys of workers in specific industries or occupations produced varying results, probably due to different types of population, exposure, and a possible "healthy worker effect" [Harber et al, 1992;Osorio et al, 19941. Based on their review of studies through 1990, Hagberg et al [1992] argue that age has not been shown to be a risk factor for CTS when the duration of exposure was controlled.…”
Section: Discussionmentioning
confidence: 98%
“…Whether this age effect [Stetson et al, 19921 is solely due to the biological aging effect or related to the length of exposure years is difficult to determine. Health surveys of workers in specific industries or occupations produced varying results, probably due to different types of population, exposure, and a possible "healthy worker effect" [Harber et al, 1992;Osorio et al, 19941. Based on their review of studies through 1990, Hagberg et al [1992] argue that age has not been shown to be a risk factor for CTS when the duration of exposure was controlled.…”
Section: Discussionmentioning
confidence: 98%
“…The literature reports that MSD problems exist both in Europe among seated cashiers (Sa È llstro È m and Schmidt 1984, Buckle 1987, Krueger et al 1988, Hinnen et al 1992) and in North America among standing cashiers (Margolis and Kraus 1987, Morgenstern and Kraus 1988, Ryan 1989, Wells et al 1990, Baron et al 1991, Harber et al 1992, Osorio et al 1994. Although comprehensive information on the severity and costs of MSD among cashiers globally does not exist, various government agencies do provide statistics on the prevalence of MSD associated with checkout work.…”
Section: Introductionmentioning
confidence: 97%
“…Da mesma forma, se conhece por estudos realizados que uma sobrecarga de horas trabalhadas, ultrapassando as 8 horas recomendadas geralmente, leva a diminuição das reações e, consequentemente, a queda na produtividade, assim como danos pessoais, principalmente quando o trabalho é intenso (BLISS, J.; DUNN, M., 2000;GRANDJEAN, 1998;HARBER, P. et al, 1992;HINNEN, U. et al, 1992).…”
Section: Introductionunclassified